2022
DOI: 10.1088/1755-1315/1027/1/012033
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between The Health of Mangrove Forests and The Level of Community Welfare

Abstract: An assessment of the forest health condition needs to be carried out to ensure that the condition of mangrove forest health is maintained. Margasari Village is where the average community works as fishermen and utilizes the mangrove forest as ecotourism. Therefore, the condition of the mangrove forest needs to be in good condition. This research was conducted in Margasari Village, Labuhan Maringgai District, East Lampung Regency. This study aims to obtain the value of mangrove forest health status and determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 20 publications
1
15
0
Order By: Relevance
“…Based on figure 2 above, it is known that there are 60 trees obtaining a value of 2 (low), 52 trees obtaining a value of 3 (moderate) and 49 trees obtaining a value of 4 (good). The difference in VCR values obtained is influenced by various factors, including plant treatments carried out by the community [6]. The VCR values obtained in this study are shown by Table 4.…”
Section: Forest Health Monitoringmentioning
confidence: 68%
See 2 more Smart Citations
“…Based on figure 2 above, it is known that there are 60 trees obtaining a value of 2 (low), 52 trees obtaining a value of 3 (moderate) and 49 trees obtaining a value of 4 (good). The difference in VCR values obtained is influenced by various factors, including plant treatments carried out by the community [6]. The VCR values obtained in this study are shown by Table 4.…”
Section: Forest Health Monitoringmentioning
confidence: 68%
“…FHM methods begins with determining the sampling index of the forest to look for its health status, then the assessment of the crown condition is carried out based on ecological parameters [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23]. The crown condition is described by five ecological parameters namely : live crown ratio, foliage transparency, crown density, crown diameter, and the dieback [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Farmers have the lowest average awareness score. Maulana et al (2022) added that protecting the forest is a must for the community because the forest acts as a provider of various needs. In contrast, farmers in Sidomulyo Hamlet view the forest as a provider of various needs that can be exploited.…”
Section: Community Efforts To Reduce Wild Grazingmentioning
confidence: 99%
“…Tree damage condition (CLI), crown condition, and other variables are used as criteria for forest health indicators (VCR). Based on the criteria for damage with forest health monitoring approaches, the tree damage assessment comprises the location of the damage, the type of damage, and the level of tree damage in each tree (Forest Health Monitoring)[12]. Damage that satisfies the criteria in accordance with pre-established requirements is the sort of damage assessed[18].The damage index (IK) at the index cluster-level damage are used to examine tree damage (CLI), the plot-level damage index (PLI) and the tree level (TLI).…”
mentioning
confidence: 99%